2004
DOI: 10.4049/jimmunol.173.4.2715
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Innate Immunity by Acute Ethanol Administration: A Global Perspective and a New Mechanism Beginning with Inhibition of Signaling through TLR3

Abstract: Excessive consumption of ethanol (EtOH) suppresses innate immunity, but the mechanisms have not been fully delineated. The present study was conducted to determine whether EtOH suppresses TLR signaling in vivo in mice and to characterize the downstream effects of such suppression. Degradation of IL-1R-associated kinase 1 induced by a TLR3 ligand in peritoneal cells (∼90% macrophages) was suppressed by EtOH. Phosphorylation of p38 kinase in peritoneal macrophages (F4/80+) was suppressed, as was nuclear transloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 66 publications
6
72
0
Order By: Relevance
“…38 In addition, Pruett et al 39 recently reported that ethanol inhibited poly I:C activation of Toll-like receptor 3 (TLR3) signaling in macrophages. It is plausible then to speculate that ethanol may also inhibit TLR3 signaling in NK cells, contributing to ethanol inhibition of NK cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…38 In addition, Pruett et al 39 recently reported that ethanol inhibited poly I:C activation of Toll-like receptor 3 (TLR3) signaling in macrophages. It is plausible then to speculate that ethanol may also inhibit TLR3 signaling in NK cells, contributing to ethanol inhibition of NK cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol has been reported to inhibit the functioning of multiple components of the immune system; both innate immune cells, such as neutrophils, monocytes, macrophages, and dendritic cells (DCs), and B and effector T cells involved in adaptive immunity are adversely affected in both in vitro and in vivo ethanol exposure models. Several signaling pathways found in innate immune cells, involving cytokines, Toll-like receptors (TLRs) 2, 3, 4, and 9, and their downstream targets, such as NF-B as well as signal transducers and activators of transcription (STAT), have been reported to be affected negatively by acute and chronic ethanol exposure (11,12,(22)(23)(24)27). In addition, secretion of the proinflammatory cytokines interleukin-1␤ (IL-1␤), tumor necrosis factor alpha (TNF-␣), and IL-6 has been found to be altered as well (1).…”
mentioning
confidence: 99%
“…This in turn inhibited the progression of inflammation and liver damage [81,82]. Interestingly, in an alcohol-induced liver injury model, TLR3 signalling activated HSC and Kupffer cells to produce the antiinflammatory cytokine IL-10, which subsequently antagonized TLR4 signalling and minimized liver injury [84]. Another study showed that poly(IC) treatment suppressed inflammation and fat accumulation in the liver of alcohol-injured mice [80].…”
Section: Livermentioning
confidence: 96%